Analisis Efektivitas Penerapan Crew Management System (CMS) terhadap Monitoring Dokumen Kru Kapal LNG di PT. X - KINANTI, ANINDYA FATIKA; NUGRAHA, BUGI; RATNANINGSIH, DYAH; SIANTURI, INTAN (Sekolah TInggi Ilmu Administrasi dan Manajemen Kepelabuhan (STIAMAK) Barunawati Surabaya, 2025)
Crew Management System is a document management system at PT. X in monitoring LNG ship crew documents. The implementation of the system at PT. X has several obstacles related to the effectiveness of document monitoring that hinders the smooth running of document management activities for crew debriefing preparation. The purpose of this study is to determine the implementation, role, and analysis of the effectiveness of the system in relation to the ship crew document monitoring at PT. X. The research method uses a qualitative method with a qualitative descriptive approach through case studies. Data collection for the study was carried out through interviews, field observations, documentation, and identification of research documents. The results of the research data collection as primary data were obtained from sources and field data at the company or PT. X, secondary data in the form of documentation. The results of the study indicate that Crew Management System has a major influence on crew document monitoring activities. However, the effectiveness of the system implementation is obtained from obstacles to the implementation of crew document monitoring at PT. X.